2023
DOI: 10.1007/s10103-023-03706-4
|View full text |Cite
|
Sign up to set email alerts
|

Single session of laser photobiomodulation for symptom management of oral lichen planus: a retrospective study

Abstract: This study aimed to evaluate the effectiveness of a single session of laser photobiomodulation (PBM) with flat top handpiece in reducing painful symptoms in patients with Oral Lichen Planus (OLP). The clinical charts of 20 patients of the Dental Clinic of University of Padua (Italy) who underwent a single laser PBM to manage OLP symptomatology were retrospectively analyzed. A 980 nm diode laser and a flat top handpiece with a 1-cm2 spot area were employed to perform the PBM with a single session protocol. VAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, a recent paper reported that a single session of laser PBM may be safe and effective in reducing pain for symptomatic OLP patients. 30 However, the study did not have any control arm; hence, further, randomized controlled studies with placebo or topical corticosteroids as a comparison would be necessary to provide sound evidence on the utility of the single session on PBMT. Wavelength is also considered one of the most critical factors in all types of phototherapy, and the recommended wavelength should be 600 and 700 nm to treat superficial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent paper reported that a single session of laser PBM may be safe and effective in reducing pain for symptomatic OLP patients. 30 However, the study did not have any control arm; hence, further, randomized controlled studies with placebo or topical corticosteroids as a comparison would be necessary to provide sound evidence on the utility of the single session on PBMT. Wavelength is also considered one of the most critical factors in all types of phototherapy, and the recommended wavelength should be 600 and 700 nm to treat superficial tissue.…”
Section: Discussionmentioning
confidence: 99%